(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2026)
This research attempts to address the electronic comic story as an ideal model for applying the data of functional grammar theory to its text, showing its distinction from the ordinary story, and from the paper story, and the development of employing the cognitive template in it, which makes it a means to strengthen the linguistic, cognitive, cognitive, logical, social and imaginative abilities of the child faster and more effectively than ordinary stories. The research followed the descriptive-analytical approach to track the grammatical manifestations in the electronic short story, providing a definition of the story in its general sense in language and terminology, and comparing it with the term electronic comics, and studying the functional grammar of electronic comics through the application of functional grammar categories in the analysis of a model of a religious educational story whose purpose is to activate the feeling of love for doing good by teaching the child the meaning of harming others, and teaching them other socio-religious values, such as the commitment to do good in secret and not to be hurt.